Influence of Materials and Scale Factor on Failure of K-shaped Nodes of Pipe Concrete Bridges: Effectiveness of Design Parameters - Spivak, D. S.; Kliuchnyk, S. V. (Science and Transport Progress, 2025)
Purpose. The paper aims to analyze the stress-strain state of K-shaped nodes of pipe-concrete structures using finite element modeling with consideration of nonlinear characteristics of materials, which, in turn, requires an assessment of the influence of materials and node sizes on the operation of hollow braces in lattice bridge structures. Methodology. Numerical modeling of the stress-strain state of K-shaped nodes of pipe concrete belts in the ANSYS program was performed. Two classes of concrete (C16/20 and C50/60) and two steel grades (16D and 10HSND) were used for the analysis, which were modeled using the Drucker-Prager plasticity criterion for concrete and the multilinear isotropic strengthening tool for steel. We prepared 12 variants of the node models with different material characteristics and two dimensional scales. To approximate the real state, the assemblies were loaded in two stages: first, the belt was loaded, and then the braces were loaded until they failed. Findings. The calculations showed that the deformation of hollow specimens of nodes corresponds to the laboratory experiments of other authors. The effect of concrete filling on compressed and tensile braces was significant, especially for compressed braces, where the effect reached 20.8%. C50/60 concrete does not always improve performance, sometimes being inferior to C16/20 concrete. Increasing the node size has a positive effect on concrete efficiency, particularly for compressed struts, where the increase was up to 12.3%. Increasing the strength of steel from 16D to 10KhSND for tensile braces showed an efficiency of 0 to 8.6%, and for compressed braces - up to 22.8%. Stress plots along the weld showed that concrete helps to distribute stresses evenly in both compressed and tensile braces. Originality. The paper analyzes the influence of materials and geometry of steel assemblies partially filled with concrete on the performance of hollow braces, with special attention paid to the little-studied factor of the assembly size. Practical value. Thanks to the finite element nonlinear analysis and the application of Ukrainian regulations and European standards, the principles of optimal selection of concrete and steel classes for pipe concrete K-shaped assemblies have been established. This makes it possible to ensure the reliability of modern bridge lattice structures, increase their efficiency and cost-effectiveness.